Valorization of waste from coconut palm cultivation as source of cellulose to papermaking - Forero-Sandoval, I. Y.; Duarte-Aranda, S.; Canche-Escamilla, G. (International journal of environmental science and technology (Tehran), 2025)
The valorization of waste can help to mitigate the environmental impact by the manufacture of new products. The main objective of this work is to establish the basis for the integral utilization of wastes from the coconut palm industry. This study presents an analysis of coconut palm (Cocos nucifera L.) wastes in terms of their chemical composition, cellulose obtention and their use in papermaking. The wastes were classified into leaves (CPL), petiole (CPP), trunk (CPT) and fruit (CPF). The content of extractives, lignin, cellulose, and hemicellulose was determinate according to TAPPI methods. Cellulose by papermaking was obtained through an alkaline hydrothermal process (AHTP). Analyses were performed using a scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), X-ray diffraction (XRD), and mechanical tensile tests. Results revealed significant variations in the chemical composition among the wastes studied, with a notable high content of lignin (~ 30%) for CPT and CPF, and high extractives (~ 22%) for CPL. Cellulose extracted by AHTP exhibited yield variations ranging from 20 to 33%, with the highest efficiency observed for CPT. Fiber dimensions varied, and the paper made from cellulose derived from CPL demonstrated superior performance. It exhibits an apparent density of 289 kg/m 3 , a tensile index of 13.5 Nm/g and a tear index of 3.1 Nm 2 /kg. This study employs a systematic analysis of coconut palm waste. The identical conditions maintained for each group allow the observed differences and similarities to be attributed to the intrinsic characteristics of the subjects rather than to external factors. Graphical abstract